Making Deals in Court-Connected Mediation: What's Justice Got to Do With It? - Nancy A. Welsh (Washington University Law Quarterly, 2001)
This Article argues that particularly within the context of the courts, mediation should be expected to deliver to disputants an experience of justice, more commonly referred to as procedural justice. This Article applies the research findings and theories from the procedural justice literature to the current evolution of court-connected mediation. The analysis reveals that some of the changes that streamline bargaining—the dominant participation of disputants’ attorneys and the reduced role of the disputants, the eventual use of evaluative interventions, and the prevalence of monetary (noncreative) outcomes—are not necessarily inconsistent with procedural justice considerations. Ultimately, this Article argues that choices need to be made to keep court-connected mediation from continuing its headlong evolution (or devolution) into becoming just another bargaining session.
Keywords: Mediation; Court administration; Compromise (Law); Civil procedure; Decision making; Justice